Stress Coping Strategies used by Students of State Agricultural Universities (SAUs) of Northern India - Anjali Negi; Kanwaljit Kaur (Indian Journal of Extension Education, 2018)
The study was conducted to identify the stress coping strategies used by the students to cope up with stress. Thestudy was conducted in three colleges of the four State Agricultural Universities of Northern India selected purposively, namely G.B.P.U.A.T., Pantnagar (Uttarakhand), CCS Haryana Agricultural University, Hisar (Haryana), Maharana Pratap University of Agriculture and Technology, Udaipur (Rajasthan) and Punjab Agricultural University, Ludhiana (Punjab).A sample of 540 students was selected through stratified random sampling technique. Three hundred sixty undergraduate students (third year) and 180 post-graduate students (3rd semester) were selected randomly. Thirty undergraduate and fifteen post-graduate students were selected randomly from each college to make a total of 360 and 180 respectively. Five major strategies i.e. relaxation strategies, social support strategies, personal strategies, diet and exercise strategies and psychological strategies were identified. Data were collected through distributed questionnaire technique. The findings of the study revealed that all under-graduateand post-graduate students were practicing positive stress coping strategies such as “listening to music”, “seeking out friends for conversation”, “using past experience to handle problems” and “trying to look on the bright side of the things”. However, meditation and yoga personal sub strategies were found to be least preferred by the students to cope up with stress.